2022
DOI: 10.1111/vde.13135
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for meticillin‐resistant Staphylococcus aureus (MRSA) carriage in MRSA‐exposed household pets

Abstract: Background: Household pets can carry meticillin-resistant Staphylococcus aureus (MRSA) introduced to the home by their human companions. Specific factors promoting pet carriage of this pathogen have not been fully elucidated.Objective: This study evaluated MRSA cultured from pets and the home environment in households where a human infected with MRSA had been identified, and aimed to determine potential risk factors for pet MRSA carriage. Materials and Methods: Humans diagnosed with community-associated MRSA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…This may suggest that birthplace may be a stronger contributing factor for the genotype of a S. aureus SSTI than the current geographic location of residence and environment. However, Kadariya et al investigated S. aureus nasal carriage from two geographic populations, Bhutanese refugees living in Nepal and Bhutanese refugees living in Ohio, and found that the most common spa types were different in the two populations [33], suggesting a stronger impact on carriage is tied to current environmental exposures.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that birthplace may be a stronger contributing factor for the genotype of a S. aureus SSTI than the current geographic location of residence and environment. However, Kadariya et al investigated S. aureus nasal carriage from two geographic populations, Bhutanese refugees living in Nepal and Bhutanese refugees living in Ohio, and found that the most common spa types were different in the two populations [33], suggesting a stronger impact on carriage is tied to current environmental exposures.…”
Section: Discussionmentioning
confidence: 99%